Young Euro Classic Festival - With Dmitry Masleev, Nils Landgren... With orchestras from Turkey, Japan, Russia, Moldova, and Asia - Verdi, Giuseppe; Beethoven, Ludwig van; Tchaikovsky, Pyotr Ilyich; Tchaikovsky, Pyotr Ilyich; Khoji, Rkinash; Weinberg, Mieczysław; Wong, Chun-Wai (EuroArts, ZDF, 2017)
For the 17th Young Euro Classic--one of the world's greatest classical musical festivals for young musicians--orchestras from Turkey, Japan, Russia, Moldova, and Asia share one stage. Side by side with the great conductors and soloists, hundreds of young people filled Berlin's Konzerthaus to perform music of different periods and styles from the western and eastern classical canons. The festival highlights begin with Verdi's unforgettable Overture to La forza del destino. Next comes Beethoven's cantata for choir and orchestra "Meeresstille und glückliche Fahrt", a relatively unknown but magnificent work inspired by two poems by Goethe. Tchaikovsky's First Piano Concerto is then performed by the marvelous young Russian pianist Dmitry Masleev. The second half is devoted to unconventional works outside of the Western classical repertoire. The Georgian and Mingrelian Songs--written by Rkinash Khoji and arranged in a jazz style by pianist Giorgi Mikadze--draw their inspiration from Georgian folk music. We journey further east with Mieczysław Weinberg's Rhapsody on Moldovian Themes, and eventually arrive in Asia with Chun-Wai Wong's As the Heart Soars. The impetuousness of this modern symphonic poem reveals Hong Kong's incredible multiculturalism, a meeting point where a wide range of musical styles fuse to create new and fascinating musical possibilities
Keywords: concert; Internet videos